3D In Vitro Human Organ Mimicry Devices for Drug Discovery, Development, and Assessment. (10th August 2020) - Rodriguez-Garcia, Aida; Oliva-Ramirez, Jacqueline; Bautista-Flores, Claudia; Hosseini, Samira
Abstract : The past few decades have shown significant advancement as complex in vitro humanized systems have substituted animal trials and 2D in vitro studies. 3D humanized platforms mimic the organs of interest with their stimulations (physical, electrical, chemical, and mechanical). Organ-on-chip devices, including in vitro modelling of 3D organoids, 3D microfabrication, and 3D bioprinted platforms, play an essential role in drug discovery, testing, and assessment. In this article, a thorough review is provided of the latest advancements in the area of organ-on-chip devices targeting liver, kidney, lung, gut, heart, skin, and brain mimicry devices for drug discovery, development, and/or assessment. The current strategies, fabrication methods, and the specific application of each device, as well as the advantages and disadvantages, are presented for each reported platform. This comprehensive review also provides some insights on the challenges and future perspectives for the further advancement of each organ-on-chip device.